2016
DOI: 10.1016/j.crpv.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

First approach to bone histology and skeletochronology of Equus hemionus

Abstract: a b s t r a c tHistological approaches to extant mammalian life histories (LHs) provide the basis for reconstructing LHs of fossil mammals. They are of special interest in lineages such as perissodactyls that played a key role in fossil ecosystems. We studied an ontogenetic series of Equus hemionus (Asiatic wild ass), the most appropriate extant representative of fossil horses. We analyzed growth marks in femora of 10 specimens of different ontogenetic stages and habitats. Bone tissue types and vascular canal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 39 publications
0
42
0
Order By: Relevance
“…) but has been shown not to be fully reliable in equids of a known age (Nacarino‐Meneses et al. 2016a). Here, we discuss the results of our approach for the red deer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…) but has been shown not to be fully reliable in equids of a known age (Nacarino‐Meneses et al. 2016a). Here, we discuss the results of our approach for the red deer.…”
Section: Discussionmentioning
confidence: 99%
“…Specimens younger than 6 months showed this shift in the central part of the cortex, which supports its non-cyclical origin. The change of tissue, both in femora and tibiae, often accompanied by radial canals, could be produced by the beginning of locomotion and weight bearing in newborns (Nacarino-Meneses & K€ ohler, 2018).…”
Section: Materials Of Unknown Agementioning
confidence: 99%
“… Martinez-Maza et al (2014) identified ontogenetic changes in bone structure and growth rate and distinguished three histological stages of ontogeny corresponding to immature, subadult, and adult individuals. Nacarino-Meneses, Jordana & Köhler (in press) studied an ontogenetic series of Equus hemionus (Asiatic wild ass). They analysed growth marks in femora of different ontogenetic stages.…”
Section: Bone Histology Of Extinct and Extant Cynodont Cladesmentioning
confidence: 99%
“…The study of bone growth marks (BGMs) is nowadays the focus of many investigations due to its potential to reconstruct many aspects of the life history of present and past vertebrates ( Amson et al, 2015 ; Kolb et al, 2015a ; Woodward et al, 2015 ; Jordana et al, 2016 ; Moncunill-Solé et al, 2016 ; Nacarino-Meneses, Jordana & Köhler, 2016 ; Orlandi-Oliveras et al, 2016 ). These histological features, which record cyclic variation in bone growth rate, can take the form of “lines of arrested growth” (LAGs) or of “annuli” within the cortical bone ( Castanet et al, 1993 ).…”
Section: Introductionmentioning
confidence: 99%
“…The histological analysis of bones for this kind of research in mammals is still little explored in comparison with other vertebrate groups ( Castanet et al, 2004 ; Kolb et al, 2015a ; Jordana et al, 2016 ). However, since the study of Köhler et al (2012) that demonstrated the correlation between cyclical bone growth and seasonal physiology in a wide sample of ruminants, the number of histological works in extant ( Marín-Moratalla, Jordana & Köhler, 2013 ; Marín-Moratalla et al, 2014 ; Jordana et al, 2016 ; Nacarino-Meneses, Jordana & Köhler, 2016 ) and extinct mammals ( Martínez-Maza et al, 2014 ; Kolb et al, 2015b ; Amson et al, 2015 ; Moncunill-Solé et al, 2016 ; Orlandi-Oliveras et al, 2016 ) has considerably increased. Among all mammalian clades, members of the family Equidae play a key role in extant and fossil ecosystems ( MacFadden, 1992 ; Downer, 2014 ).…”
Section: Introductionmentioning
confidence: 99%